1995
DOI: 10.1017/s0022112095004241
|View full text |Cite
|
Sign up to set email alerts
|

Viscous oscillatory flow about a circular cylinder at small to moderate Strouhal number

Abstract: The transient flow field caused by an infinitely long circular cylinder placed in an unbounded viscous fluid oscillating in a direction normal to the cylinder axis, which is at rest, is considered. The flow is assumed to be started suddenly from rest and to remain symmetrical about the direction of motion. The method of solution is based on an accurate procedure for integrating the unsteady Navier–Stokes equations numerically. The numerical method has been carried out for large values of time for both moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
1
13
1
Order By: Relevance
“…Also, the length of the separated zone is relatively independent of KC. This is in contrast to higher Reynolds number (Re > 100) studies [6][7][8] where vortex formation and shedding are primarily dependent on KC.…”
contrasting
confidence: 68%
See 2 more Smart Citations
“…Also, the length of the separated zone is relatively independent of KC. This is in contrast to higher Reynolds number (Re > 100) studies [6][7][8] where vortex formation and shedding are primarily dependent on KC.…”
contrasting
confidence: 68%
“…Few studies [6][7][8] have been reported in the literature on the pulsatile flow past the stationary cylinder for Reynolds number (Re) >100 focusing on marine applications. As TAL operating Reynolds number is between 5 and 10, flow dynamics is expected to be different and no correlation can be made from studies available in the literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a triad of two geometrical parameters and a velocity related parameter (Reynolds number or velocity itself) are not sufficient to define the problem entirely. Indeed a large body of literature related to the oscillatory flows past cylinders (Bearman et al 1985, Badr et al 1995, Lin et al 1996, Iliadis and Anagnostopoulos 1998 suggests that frequency of the forcing flow must appear in the problem description in one form or another. A widely accepted parameter of this kind is Keulegan-Carpenter number (KC), usually defined as (velocity)/(frequency x dimension).…”
Section: Similarity Issues -Geometry and Flow Parametersmentioning
confidence: 99%
“…oscillatory flow forcing), not the frequency of the vortex shedding often investigated in steady flows past bluff bodies. This "forcing" Strouhal number has already been used such as in the study of the oscillatory flow around a circular cylinder (Badr et al, 1995).…”
Section: Normalisationmentioning
confidence: 99%